Reading the discourse of reading: a window on the meaning construction processes of third year learners of French - Hood, Philip (2000)
The main study of the thesis seeks to gain insights into the reading behaviour of 27 adolescent learners of French, who were recorded while completing four reading tasks, 2 individually and 2 in small groups. The transcripts are analysed from four perspectives. Firstly (as a baseline for the other perspectives) a quantitative approach examines factors surrounding relative success in the tasks. Secondly a coding system (Pressley and Afflerbach, 1995) is used to analyse strategy use by a selection of subjects in both individual and group contexts. Thirdly, the nature and quality of the talk of four of the groups is explored using Mercer's (1995) three categories of talk and aspects of Almasi's (1995) work on sociocognitive conflict. Finally the problem-solving discourse of the transcripts is analysed in two ways- using a concordancing program and by investigating the roles in decision-making of key individuals in four different groups through discourse analysis techniques. A discussion chapter seeks to draw together the findings from these four perspectives. The processes used for the study are also discussed through chapters on relevant literature, on methodology and by a report of an earlier preparatory study.